Study of Phytochemical, Anti-Microbial, Anti-Oxidant, Phytotoxic, and Immunomodulatory Activity Properties of Bauhinia variegata - Jaya Bhandari; Pratiksha Thapa; Prasodhan Niraula; Nita Thapa; Nikita Shrestha; Bhupal Govinda Shrestha (Journal of Tropical Life Science, 2017)
There is growing interest in the use plants for the treatment and prevention of cancer and are currently being evaluated as promising anticancer agents. In this paper, we investigated the anti-microbial, anti-oxidant, phytotoxic and immunomodulatory of plant Bauhinia variegata and also established the presence of important phytoconstituents which might signify its anticancer property. Phytochemical screening, anti-microbial assay, phytotoxicity assay, anti-oxidant assay and immunomodulatory analysis was done according to the protocol established at Department of Biotechnology, Kathmandu University and Panjwani Center for Molecular Medicine and Drug Research, University of Karachi, Pakistan.In the phytochemical screening, we observed the presence of different phytochemicals like steroids, terpenoids, flavonoids, reducing sugars and glycosides. In case of Antimicrobial assay, the plant was found to be most effective against B.cereus with the highest zone of inhibition (ZOI) of 12mm and against Rhizopus with ZOI of 11mm. During the antioxidant assay in comparison to Ascorbic acid; at highest concentration, the scavenging activity shown by the plant Bauhinia variegata are 43.38% as compared to ascorbic acid 89.25%. In the Immunomodulatory assay at the highest concentration i.e. 250 Âµg/ml, the plant showed 75.1% effect, which showed that the plant has potential anti-inflammatory potential. In phytotoxicity assay, Bauhinia variegata showed 20% phytotoxicity. Bauhinia variegata has thus been proven to be an important candidate to be used as an antimicrobial, antioxidant, anti-inflammatory, phytotoxic and anticancer agent. Separation of pure compounds with bioassay guided extraction, spectrometric analysis and subsequent cytotoxicity assay of the pure bioactive compounds from Bauhinia variegate is highly recommended as crude extract itself showed promising phytotoxicity and other pharmaceutical potential.